2004
DOI: 10.1037/0735-7028.35.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Bibliotherapy for Depression: A Meta-Analysis.

Abstract: Do you want to use bibliotherapy with clients but wonder about the size and mechanism of effectiveness? The authors report a meta-analysis of 29 outcome studies of cognitive forms of bibliotherapy for depression. Seventeen studies with stronger research designs (pretest-posttest waiting list control group) yielded a respectable effect size of 0.77, considered the best estimate of effect size from this study. This result compares favorably with outcomes from individual psychotherapy. In light of the substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
104
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 44 publications
6
104
0
3
Order By: Relevance
“…MBCT self-help (MBCT-SH) resources including books, CDs, phone apps and online packages are easily accessible and popular. However, while there is evidence that self-help cognitive behavioural therapy (CBT-SH) is effective for depression (Gregory, Canning, Lee & Wise, 2004) and anxiety disorders (Lewis, Pearce & Bisson, 2012), little is known about the effectiveness of MBCT-SH. Although research into MBCT-SH is in its infancy, there is emerging evidence that self-help books based on Acceptance and Commitment Therapy (ACT), an approach which includes mindfulness principles, can improve anxiety and depression in community (Fledderus, Bohlmeijer, Pieterse & Schreurs, 2011) and student (Muto, Hayes & Jeffcoat, 2011) populations.…”
Section: Introductionmentioning
confidence: 99%
“…MBCT self-help (MBCT-SH) resources including books, CDs, phone apps and online packages are easily accessible and popular. However, while there is evidence that self-help cognitive behavioural therapy (CBT-SH) is effective for depression (Gregory, Canning, Lee & Wise, 2004) and anxiety disorders (Lewis, Pearce & Bisson, 2012), little is known about the effectiveness of MBCT-SH. Although research into MBCT-SH is in its infancy, there is emerging evidence that self-help books based on Acceptance and Commitment Therapy (ACT), an approach which includes mindfulness principles, can improve anxiety and depression in community (Fledderus, Bohlmeijer, Pieterse & Schreurs, 2011) and student (Muto, Hayes & Jeffcoat, 2011) populations.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliotherapy has been found to outperform assessment-only control conditions for the treatment of depression for adolescents and adults (Cuijpers, 1997;Gregory, Schwer-Canning, Lee, & Wise, 2004). One study found that CBT bibliotherapy was superior to an assessment-only control condition for adolescents with mild to moderate depressive symptoms through 1-month follow-up (Ackerson, Scogin, McKendreeSmith, & Lyman, 1998).…”
Section: Bibliotherapymentioning
confidence: 99%
“…For instance, most artistic modalities have been harnessed in therapeutic contexts, helping to ameliorate physical and mental illness, spanning art therapy (Reynolds et al, 2000), music therapy (Ruud, 2008), singing therapy (Olderog Millard & Smith, 1989), dance/movement therapy (Loman, 2005), bibliotherapy (Gregory et al, 2004), writing therapy (Pizarro, 2004), poetry therapy (Connolly Baker & Mazza, 2004), drama therapy (Schnee, 1996), and even comedy therapy (Crawford & Caltabiano, 2011). Work within these areas is certainly encompassed by positive art.…”
mentioning
confidence: 99%